Diversification of Fresh Milk into Yogurt to Increase Economic Value of Dairy Groups - Astuti, Widi; Widyastuti, Catur Rini; Putra, Muhammad Rizky Fahrizal; Nurrahman, Ahmad Rickyansyah; Firmansyah, Fariq Hammam; Ubay, Isnina Noor; Harianingsih, Harianingsih (Journal of Community Empowerment, 2025)
Low selling prices of fresh milk and the rejection of substandard milk by the Milk Processing Industry have reduced the income of dairy groups in Gunungpati, Semarang, and caused environmental problems due to milk disposal. This community service program aimed to increase the economic value of fresh milk through diversification into yogurt products. The program involved entrepreneurship motivation, assembly of a milk pasteurization unit, provision of a yogurt incubator, and hands-on yogurt production training for 20 members of a dairy processing group. The activity emphasized appropriate technology application and skill development to enable independent household-scale production. Results showed improved technical competence in yogurt processing, increased entrepreneurial motivation, and initial product trials for market testing. Fresh milk diversification into yogurt provides an alternative strategy to enhance income, reduce environmental waste, and strengthen community-based dairy business sustainability.